PENGARUH CITRA MEREK DAN KUALITAS TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Hartono, Anang; Wahyono, Wahyono (Management Analysis Journal, 2015)
The development of the business world that increasingly stringent demands companies should be able to move quickly and precisely to be able to face the competition. In fact become a leader in the market is not easy. Right marketing strategy is needed for the company to survive and compete with the hope to increase sales and customer satisfaction. Maintain the image and quality of the product is an attempt to attract purchases and customer satisfaction. This study aims to investigate the influence of brand image and quality to customer satisfaction through the purchase decision as an intervening variable. This study population are all consumers daily newspaper Suara Merdeka. Sampling by using incidental sampling technique, the number of respondents were 116 respondents. Data collection method used is the method of observation, interviews, and a questionnaire method. Path analysis Analyse the data using SPSS version 20, which used variables include brand image, quality, purchasing decisions and consumer satisfaction.